A Multivocal Literature Review of Green Election Political Education Based on Pancasila Values to Achieve Sustainability - Pratama Yoga Wica; Farid Fadillah; Novi Eka Saputri; Arif Subowo; Nurul Fajariah; Ahmad Ridhani Noorfauzi (IAIN Madura, 2025)
Pancasila-based green election reform is positioned as a strategy to strengthen democracy with integrity while simultaneously orienting toward sustainability and environmental awareness. Using the Multivocal Literature Review method, this study examined 69 secondary documents from regulations, journals, proceedings, reports, and books. This international and national literature review utilized large databases such as Scopus and Web of Science. Government documents, such as laws, regulations, and other supporting documents, were retrieved from Indonesian legal web sources. Two concepts were used: environmental and political education. These two concepts were used solely for conceptual understanding. The analysis was then conducted based on existing regulations in Indonesia, then integrated with the values ​​of Pancasila. The results show that although regulations on environmental political education exist, their implementation remains weak, and the values ​​of divinity, humanity, unity, deliberation, and justice have not been reflected in environmental election performance indicators. Key recommendations include green compliance indicators in the evaluation and ethics of organizers, low emission campaigns that are inclusive of all groups including people with disabilities, the establishment of a green election task force, the development of a green election deliberation module, and the management of campaign material waste to promote a just and sovereign green democracy in line with Pancasila.